Analysis of Phrases Based on their Forming Elements in the Film Langit Tak Selamanya Abu-Abu by Kemendikbud RI - Marshanda, Tirza; Hidayatul, Alina; Rindu, Jihanita; Jannah, Miftahul; Oxana, Oktian; Pratama, Rakha; Aisy, Rihada; Salamah, Siti; Rumboy, Yuliva; Suhita, Raheni (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this study is to analyze the film